2021
DOI: 10.3928/01477447-20201119-06
|View full text |Cite
|
Sign up to set email alerts
|

A Single Sugar-Tong Splint Can Maintain Pediatric Forearm Fractures

Abstract: Displaced pediatric forearm fractures often are treated with closed reduction and immobilization. Recent literature demonstrates no difference in maintaining alignment or needing repeat intervention in patients immobilized with either a single sugar-tong splint or a long-arm cast, but most series include patients with distal fractures. This study included patients 3 to 15 years old who underwent closed reduction and immobilization for displaced midshaft or proximal forearm fractures. Radiographs from the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…The aforementioned authors retrospectively studied the fixation results with SSTS (n=51) and LAC (n=70) in pediatric forearm fractures with a larger number of patients later and reported that both methods were acceptable and equivalent methods of immobilization for these injuries. [18] Dittmer et al [9] published the results of 168 pediatric forearm fractures immobilized with STS and reported that STS was effective in maintaining the reduction of pediatric forearm fractures, similar to published rates for casting. Of note, relative to the study of Dittmer et al, [9] there were more cases in our study and these authors did not have a control group.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The aforementioned authors retrospectively studied the fixation results with SSTS (n=51) and LAC (n=70) in pediatric forearm fractures with a larger number of patients later and reported that both methods were acceptable and equivalent methods of immobilization for these injuries. [18] Dittmer et al [9] published the results of 168 pediatric forearm fractures immobilized with STS and reported that STS was effective in maintaining the reduction of pediatric forearm fractures, similar to published rates for casting. Of note, relative to the study of Dittmer et al, [9] there were more cases in our study and these authors did not have a control group.…”
Section: Discussionmentioning
confidence: 74%
“…Of note, relative to the study of Dittmer et al,[ 9 ] there were more cases in our study and these authors did not have a control group. Moreover, the studies of Dittmer et al[ 9 ] and Murphy et al[ 7 , 18 ] consist of all forearm fractures, while the current study includes more specific and regionally homogeneous distal forearm fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that SSTSs are effective for the treatment of forearm and wrist fractures [ 5 , 7 ]. Moreover, DSTSs are preferred for patient groups similar to those treated with SSTSs and are successful at immobilization [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fractures near the physis in young children have the greatest potential to remodel. Most pediatric distal forearm fractures can be treated nonoperatively [13] by casting or splinting [14] with or without a closed reduction. Loss of alignment of distal radius fractures after nonoperative treatment is common, with a rate reported between 7% and 91% [13,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%